Illousion And Truth About Polarisation Of Education In Korea - Kim, Bok-rae (Advances in Social Sciences Research Journal, 2018)
Purpose: The goal of this paper is firstly to examine the deepening “educational gap” between disadvantaged and privileged pupils; secondly to view the impacts of government standardization policy on the extension of educational inequalities; thirdly to suggest problem-solving directions to reduce the education divide in a country where education levels show a strong correlation with income levels Methodology: This study proposes the solution plans to reduce the education divide by using scholarly literature review, statistical data and politico-phenomenological methodology under the Korean context where there is deep-rooted antagonism between the two leftist and rightest camps. Main Findings: We can expect the possibility of building a solidaristic/cooperative leapfrogging strategy between two opposed camps to jointly cultivate future-oriented talented individuals (democratic citizens and enterprising persons), beyond untying the Gordian Knot of private education. Practical Implications: These results offer useful guidance for countries with similar educational environments with the increase in NEET (not in education, employment, or training). Novelty/Originality of this study: A tendency to criticize Korean education policy as neoliberal en bloc is sweeping over the current Korean education world, but Korean education cannot be conceived as entirely neoliberal. This study elucidates the said criticism itself is now operating as another ideology to bind teacher unions under the banner of anti-neoliberalism, through metaphysical discourse and policy analysis. Research limitation: This study is predominately focused on the Korean context. There is no truth, however, that one learns by comparing; so next, I plan to look for undertaking a comparative study in East Asia.